SELECTIVE ESTROGEN RECEPTOR MODULATORS; ROLE OF SIDE CHAIN IN ACTIVITY MODULATION - Sharma, Preeti; Kumar, Pradeep; Sharma, Rachna; Dikshit, Dinesh K (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Selective estrogen receptor modulators (SERMs) are a class of molecules that activate estrogen receptors (ER), impacting differently on different tissues. Upon binding to ER, the ligand-receptor complex may present various conformations due to the presence of two different kinds of ERs. Few of these ligands show estrogenic effects, whereas others will inhibit the action of estrogens. Researchers are working in the direction to generate the SERMs that have a desirable estrogen-like effects on the various sites i.e., bones, improving lipid profile, reduce hot flushes, but do not act like estrogens in unwanted ways i.e., causing breast cancer, uterine endometrial proliferation. Given the comprehensive nature of this article, it is not our intention to revisit many of the issues relating to SERMs, which have already been covered in detail. Rather this article focuses on the aspect that ligand-mediated structural perturbations in and around the ligand binding pocket, contributed by the side chain effects lead to receptor antagonism. Adjusting the balance of these effects may provide a novel strategy for designing of improved SERMs. In the light of this, the article will provide an overview of the SERMs and their structural diversity. Keywords: Ligand and estrogen receptor, Side chain of selective estrogen receptor modulators, Selective estrogen receptor modulators, Mechanism of action.